Commercially available versus home produced egg media for isolation of mycobacteria. Issue 6 (June 1995) - Harris, G; Rayner, A; Watt, B
Abstract : AIMS--To compare the growth of clinical isolates of mycobacteria on in-house and commercial egg media. METHODS--Fresh test media were inoculated with dilutions of the test organisms and growth, colonial morphology and microscopic appearance were compared blindly by two observers. The process was repeated after the test media had been stored for three months. The user friendliness of each of the test media was also assessed. RESULTS--There was no difference in the microscopic appearance of any given mycobacterial species between different media. All of the test media grew the test species, although Mycobacterium bovis required four weeks on BioMerieux media, compared with two weeks on the other media. There was little obvious effect of storage on any of the media, except with M kansasii. Individual species gave characteristic colonial appearances on inhouse media; all of the commercial media gave non-specific colonial appearances that made presumptive identification very difficult. There were clear differences in the user friendliness of different media. CONCLUSIONS--Although commercially available egg media in general gave good growth of mycobacteria, only in-house media combined good growth with useful colonial features.